The long-run behaviour of the terms of trade between primary commodities and manufactures : a panel data approach - Iregui, Ana María (2018)
This paper examines the Prebisch and Singer hypothesis using a panel of twenty-four commodity prices from 1900 to 2010. The modelling approach stems from the need to meet two key concerns: (i) the presence of cross-sectional dependence among commodity prices; and (ii) the identification of potential structural breaks. To address these concerns, the Hadri and Rao (Oxf Bull Econ Stat 70:245–269, 2008) test is employed. The findings suggest that all commodity prices exhibit a structural break whose location differs across series, and that support for the Prebisch and Singer hypothesis is mixed. Once the breaks are removed from the underlying series, the persistence of commodity price shocks is shorter than that obtained in other studies using alternative methodologies.